The interplay between firms' capabilities and ownership in explaining environmental performance - Beatriz Forés; César Camisón Zornoza; José María Fernández-Yá\~nez (European Journal of Management and Business Economics (EJM&BE), 2025)
Purpose - This study empirically assesses the effects of two key types of organizational and managerial capabilities-dynamic capabilities, and coordination and cohesion capabilities-on environmental performance, considering the moderating effect of family ownership. By applying the tenets of the natural resource-based view and the dynamic capabilities theory, this paper offers new insights into the topic. Design/methodology/approach The article presents empirical evidence from a survey of 1,019 firms operating in the Spanish tourism sector analyzed using multiple linear regression. Findings Overall, our results show that both dynamic capabilities and coordination and cohesion capabilities have direct and synergetic positive effects on environmental performance. In addition, the results confirm recent studies that report conflicting evidence on how family ownership affects environmental performance: family ownership is found to exert a distinct direct effect on environmental performance and on the development and application of the capabilities required to improve such performance. Originality/value This article sheds light on the conceptual frontiers between the different types of capabilities, as well as provides practical ways of measuring them. The article also brings evidence to bear on the debate concerning the direct and moderating effect that family ownership exerts on the relationship between both types of capabilities over environmental performance. The results of this analysis confirm the complexity of the family ownership effect on this aspect, and provide important insights for both business practitioners and academics.
Keywords: 650; Coordination and cohesion capabilities; Dynamic capabilities; Environmental performance; Family business; Tourism sector